2020
DOI: 10.15698/mic2020.11.734
|View full text |Cite
|
Sign up to set email alerts
|

Structural insights into the architecture and assembly of eukaryotic flagella

Abstract: Cilia and flagella are slender projections found on most eukaryotic cells including unicellular organisms such as Chlamydomonas, Trypanosoma and Tetrahymena, where they serve motility and signaling functions. The cilium is a large molecular machine consisting of hundreds of different proteins that are trafficked into the organelle to organize a repetitive microtubule-based axoneme. Several recent studies took advantage of improved cryo-EM methodology to unravel the high-resolution structures of ciliary complex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 142 publications
3
8
0
Order By: Relevance
“…We examined the cilia in spermatocytes in Pieris brassicae , also known as the cabbage butterfly or large white butterfly, a common agricultural pest native to Europe, Asia, and north Africa. While our analysis confirmed that P. brassicae spermatocytes have long cilia that persist in meiotic division, we also found that they contain thin filamentous structures of electron dense material at the base of the CLRs and along the ciliary membrane of the elongating CLRs that appear to be analogous to the IFT trains first observed in Chlamydomonas (Petriman and Lorentzen, 2020; Scholey, 2003). The findings reported here for P. brassicae provide new insights into a potential role for IFT in insect spermatocytes and opens new questions about differential involvement of IFTs in Drosophila spermatogenesis versus other systems.…”
Section: Introductionsupporting
confidence: 83%
See 2 more Smart Citations
“…We examined the cilia in spermatocytes in Pieris brassicae , also known as the cabbage butterfly or large white butterfly, a common agricultural pest native to Europe, Asia, and north Africa. While our analysis confirmed that P. brassicae spermatocytes have long cilia that persist in meiotic division, we also found that they contain thin filamentous structures of electron dense material at the base of the CLRs and along the ciliary membrane of the elongating CLRs that appear to be analogous to the IFT trains first observed in Chlamydomonas (Petriman and Lorentzen, 2020; Scholey, 2003). The findings reported here for P. brassicae provide new insights into a potential role for IFT in insect spermatocytes and opens new questions about differential involvement of IFTs in Drosophila spermatogenesis versus other systems.…”
Section: Introductionsupporting
confidence: 83%
“…While our analysis confirmed that P. brassicae spermatocytes have long cilia that persist in meiotic division, we also found that they contain thin filamentous structures of electron dense material at the base of the CLRs and along the ciliary membrane of the elongating CLRs that appear to be analogous to the IFT trains first observed in Chlamydomonas (Petriman and Lorentzen, 2020;Scholey, 2003).…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…The transition zone, an intermediate region between the basal body and the axoneme, consists of transition fibers and Y-links, which act as a ciliary gate, controlling soluble proteins and selected components in and out of cilia [19][20][21]. Here, the nine microtubules of the basal body are transformed from triplets into doublets, which form the backbone of the ciliary axoneme (known as the 9 + 0 arrangement, it lacks one pair of central microtubules and dynein arms, which is different from motor cilia) [22]. In addition, the axoneme is covered with a ciliary membrane that extends to the plasma membrane, but has different components.…”
Section: The Structure Of Primary Ciliamentioning
confidence: 99%
“…Cilia are organelles that project from the cell surface with key functions in physiology and development that occur widely in eukaryotes from protists to mammals (Berbari, O'Connor, Haycraft, & Yoder, 2009; Bloodgood, 2009; Buchwalter, Chen, Zheng, & Megraw, 2016; Fisch & Dupuis‐Williams, 2011; Gerdes, Davis, & Katsanis, 2009; Ishikawa & Marshall, 2011; Jana, Bettencourt‐Dias, Durand, & Megraw, 2016; Petriman & Lorentzen, 2020; Santos & Reiter, 2008; Singla & Reiter, 2006; Vincensini, Blisnick, & Bastin, 2011). They are critical organelles for signal transduction and transmit sensory input from a variety of environmental and interorgan signals.…”
Section: Introductionmentioning
confidence: 99%